High-sensitivity microliter blood pressure sensors based on patterned micro-nanostructure arrays. Issue 9 (25th April 2020) - Yu, Nianzuo; Liu, Yongshun; Ji, Bai; Wang, Shuli; Chen, Yunyun; Sun, Tianmeng; Zhang, Junhu; Yang, Bai
Abstract : Blood pressure sensors are proposed to measure the value of central venous pressure, and diagnose the severity of hypertension, hypotension and arterial thrombosis. Abstract : Herein we present a micro-nanostructure integrated liquid pressure sensor, which features an ultra-high sensitivity of 16.71 mbar −1, a low-pressure regime of 2 mbar, a trace sample volume of less than 1.3 μL and a visible display element. The measurable pressure ranges of the sensors include not only from micro-scale fluids to bulk liquids but also from hydraulic pressures to blood pressures, opening a window for liquid pressure sensing in lab-on-chip platforms, point-of-care diagnostics, and even robotics.